2012
DOI: 10.1371/journal.pone.0031238
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotic Bacteria Produce Conjugated Linoleic Acid Locally in the Gut That Targets Macrophage PPAR γ to Suppress Colitis

Abstract: BackgroundInflammatory bowel disease (IBD) therapies are modestly successful and associated with significant side effects. Thus, the investigation of novel approaches to prevent colitis is important. Probiotic bacteria can produce immunoregulatory metabolites in vitro such as conjugated linoleic acid (CLA), a polyunsaturated fatty acid with potent anti-inflammatory effects. This study aimed to investigate the cellular and molecular mechanisms underlying the anti-inflammatory efficacy of probiotic bacteria usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 38 publications
2
114
1
2
Order By: Relevance
“…Due to potential side effects, the application of RSG in the treatment of IBD is not likely ( 61,62 ). Efforts toward the discovery of a new class of PPAR ␥ agonist that elicits therapeutic effects against IBD with limited or no adverse side effects revealed that conjugated linoleic acid (CLA) is a safer alternative to RSG in the model of spontaneous pan-enteritis and DSS-induced colitis (63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Due to potential side effects, the application of RSG in the treatment of IBD is not likely ( 61,62 ). Efforts toward the discovery of a new class of PPAR ␥ agonist that elicits therapeutic effects against IBD with limited or no adverse side effects revealed that conjugated linoleic acid (CLA) is a safer alternative to RSG in the model of spontaneous pan-enteritis and DSS-induced colitis (63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that the CLA-producing bacterium, B. breve NCIMB702258 converts linoleic acid to CLA in the murine gut, resulting in significantly elevated c9, t11 CLA in the liver [133]. Moreover, Bassaganya-Riera et al [134] demonstrated that administration of the probiotic mixture VSL#3 to mice with colitis resulted in high colonic concentrations of c9, t11 CLA and that this locally produced CLA improved colitis by activating peroxisome proliferator-activated receptor gamma (PPAR γ) in macrophages. Two studies have also reported the in vivo production of the CLA isomer, trans-10, cis-12 (t10, c12) CLA, by using two strains of human origin, L. rhamnosus PL60 and L. plantarum PL62.…”
Section: Conjugated Linoleic Acidmentioning
confidence: 98%
“…Some of these strains are contained in a bacterial mixture known as VLS#3, a probiotic with demonstrated therapeutic efficacy in patients with UC (Bibiloni et al, 2005) and in animal models of colitis (Madsen et al, 2001). Following up on these studies, we recently published novel in vivo evidence showing how VSL#3 administration changes microbial diversity and local CLA production, which results in PPARγ-dependent anti-inflammatory effects during DSS-and IL-10-deficiency-induced experimental colitis in mice (Bassaganya-Riera et al, 2012b). PPARγ is expressed in a large population of colonic cell types including epithelial cells and lamina propria mononuclear cells such as macrophages and lymphocytes.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%